Proposta de um modelo de integração QFD/TRIZ para a otimização sistemática de requisitos de engenharia :uma aplicação ao desenvolvimento de munição para o Exército Brasileiro - Oliveira, Vinicius Motta de (2017)
The development of a new product requires the definition of the features needed by the functions the product is planned to perform. Such features are expressed by requirements which must reflect not only the users whishes, but also the evolutionary trends of the product underlying technology. Therefore, it´s proposed an engineering requirements systematic optimization model based on a two-level integration of the methods Quality Function Deployment (QFD) and Theory of Inventive Problem Solving (TRIZ). At the first level, the prospective capabilities of both methods are used to identify the developing product requirements and submit them to users in order to evaluate the importance of the features they express. At the second level, the Contradiction Matrix is used to withdraw the technical contradictions between requirements through the proposition of solutions based on inventive principles in order to enable the product conception. The research is a Case Study in which the proposed model is applied to the development of a new mortar ammunition concept for the Brazilian Army.